Distortion Invariant Object Recognition Based on Mach-Zehnder Joint Transform Correlation in YIQ Colour Space - Chen, Chulung; Gu, Kaining; Fang, Jianshuen; Lee, hungcheng (European Journal of Applied Sciences, 2019)
We investigate the YIQ colour space in conjunction with average cross correlation optimization algorithm to design the reference function for pattern recognition on various views of the interested colour object. Joint transform correlation is devoted for recognition of colour targets. The reference function for each color channel is trained with true class images rotated in-plane at 2 degrees intervals between -14 degrees and 14 degrees. Results indicates the feasibility of our proposed method.